2019
DOI: 10.4300/jgme-d-19-00089.1
|View full text |Cite
|
Sign up to set email alerts
|

The Revised Medical School Performance Evaluation: Does It Meet the Needs of Its Readers?

Abstract: Background The Medical School Performance Evaluation (MSPE) is an important factor for application to residency programs. Many medical schools are incorporating recent recommendations from the Association of American Medical Colleges MSPE Task Force into their letters. To date, there has been no feedback from the graduate medical education community on the impact of this effort. Objective We surveyed individuals involved in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…A recent survey of program directors appeared to show support for continuing the process of standardizing the MSPE. 3 Many issues for continuing discussions by the medical education community remain. These include the lack of consensus regarding how schools define professionalism.…”
Section: Observationsmentioning
confidence: 99%
“…A recent survey of program directors appeared to show support for continuing the process of standardizing the MSPE. 3 Many issues for continuing discussions by the medical education community remain. These include the lack of consensus regarding how schools define professionalism.…”
Section: Observationsmentioning
confidence: 99%
“…As a tool of communication between UME and GME, an important consideration for the MSPE is the perspective of the end-user, defined as a person who uses the document in the residency selection process. In 2019, we reported on a survey of MSPE end-users in Internal Medicine (IM) [ 13 ]. Those findings indicated that the MSPE provided valuable information to end-users in their applicant selection process.…”
Section: Introductionmentioning
confidence: 99%
“…If a program has a low first‐pass success rate on specialty board qualifying examinations, these factors may be important to consider. The Medical Student Performance Evaluation (MSPE), interestingly, did not show convincing evidence that it could reliably predict future cognitive or noncognitive performance in residents despite being designed as a standardized comprehensive evaluation, although new guidelines for these letters are now being implemented at medical schools 33 . Negative and equivocal faculty comments on clerkship evaluations were associated with professionalism issues during residency.…”
Section: Discussionmentioning
confidence: 99%